2017
DOI: 10.1016/j.vetpar.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a new spot-on formulation of selamectin plus sarolaner in the treatment of naturally occurring flea and tick infestations in cats presented as veterinary patients in Europe

Abstract: Two randomised, blinded, multi-centre field studies were conducted in Europe (Germany, Italy, France, Hungary) to demonstrate the efficacy and safety of three monthly applications of a new spot-on formulation of selamectin plus sarolaner (Stronghold Plus, Zoetis) against natural flea or tick infestations in cats presented as veterinary patients. The spot-on formulation was administered at the commercial dose range of 6.0-12.0mg selamectin and 1.0-2.0mg sarolaner per kg bodyweight. In the flea study, the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
3
19
0
4
Order By: Relevance
“…The high and consistent efficacy of selemactin/sarolaner against I. ricinus [2, 7, 8] was confirmed in the present study. Three monthly treatments at the minimum recommended label dose of 1.0 mg sarolaner (and 6.0 mg/kg selamectin) resulted in a consistently high efficacy (> 95.8%) for at least 91 days.…”
Section: Discussionsupporting
confidence: 84%
“…The high and consistent efficacy of selemactin/sarolaner against I. ricinus [2, 7, 8] was confirmed in the present study. Three monthly treatments at the minimum recommended label dose of 1.0 mg sarolaner (and 6.0 mg/kg selamectin) resulted in a consistently high efficacy (> 95.8%) for at least 91 days.…”
Section: Discussionsupporting
confidence: 84%
“…Nach der Anwendung von Stronghold® Plus traten an der Applikationsstelle leichter, vorübergehender Juckreiz, leichte bis mittelgradige Alopezie und Hautrötung auf (4,15). Des Weiteren kam es bei den Katzen zu Speicheln (4,15).…”
Section: Wirkstoffe Die Für Eine Weitere Tierart Zugelassen Wurdenunclassified
“…Nach der Anwendung von Stronghold® Plus traten an der Applikationsstelle leichter, vorübergehender Juckreiz, leichte bis mittelgradige Alopezie und Hautrötung auf (4,15). Des Weiteren kam es bei den Katzen zu Speicheln (4,15). Nach versehentlicher oraler Aufnahme wurden vorübergehende gastrointestinale Effekte wie Speichelfluss, Erbrechen, weicher Kot oder verminderte Nahrungsaufnahme beobachtet (4).…”
Section: Wirkstoffe Die Für Eine Weitere Tierart Zugelassen Wurdenunclassified
See 1 more Smart Citation
“…3,10 Fleas and ticks also carry and transmit an assortment of vector-borne pathogens that can affect cats and people, including Bartonella spp., Ehrlichia spp., Rickettsia spp., Mycoplasma spp., as well as cestode, protozoal, and larial endoparasites. 1,2,4,13,14 Investigators have found that as many as 80% of eas collected from cat populations harbor feline or human pathogens of signi cance. 15 Safe and effective feline ea and tick treatment options are therefore an important component of the weeks after treatment.…”
Section: Introductionmentioning
confidence: 99%